2022
DOI: 10.1186/s13578-022-00788-5
|View full text |Cite
|
Sign up to set email alerts
|

PA2G4 promotes the metastasis of hepatocellular carcinoma by stabilizing FYN mRNA in a YTHDF2-dependent manner

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide with high mortality. Advanced stage upon diagnosis and cancer metastasis are the main reasons for the dismal prognosis of HCC in large part. The role of proliferation associated protein 2G4 (PA2G4) in tumorigenesis and cancer progression has been widely investigated in various cancers. However, whether and how PA2G4 participates in HCC metastasis is still underexplored. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…A TCGA cancer database analysis based on genes related to lipid metabolism in colon adenocarcinoma found that FYN gene expression was associated with the activation of the EMT pathway [132]. It has been shown in another study that increased FYN expression may contribute to hepatocellular carcinoma metastasis [133].The Wnt5-Fzd2-FYN-Stat3 axis contributes to the EMT program, cell migration, and multiple tumor metastases, and the FYN inhibitor Dasatinib inhibits this process [122].…”
Section: Fyn Regulates Tumor Epithelial-mesenchymal Transition (Emt) ...mentioning
confidence: 99%
“…A TCGA cancer database analysis based on genes related to lipid metabolism in colon adenocarcinoma found that FYN gene expression was associated with the activation of the EMT pathway [132]. It has been shown in another study that increased FYN expression may contribute to hepatocellular carcinoma metastasis [133].The Wnt5-Fzd2-FYN-Stat3 axis contributes to the EMT program, cell migration, and multiple tumor metastases, and the FYN inhibitor Dasatinib inhibits this process [122].…”
Section: Fyn Regulates Tumor Epithelial-mesenchymal Transition (Emt) ...mentioning
confidence: 99%
“…PA2G4 can be induced into the nucleus by the pseudogene PA2G4P4 to inhibit glioblastoma cell apoptosis [ 41 ]. It can bind YTHDF2 to increase FYN expression and promote hepatocellular carcinoma metastasis [ 42 ]. Moreover, PA2G4 is reported to be regulated by noncoding RNA [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the sum of the correlations of these 385 genes in gastrointestinal cancer, we screened the 30 genes with the strongest correlations, which are RARS1, BTF3, HSPA4, NSA2, HNRNPA1, EIF3M, CCT4, OLA1, UIMC1, G3BP1, NACA, RSL1D1, ETF1, MRPS27, RBM22, CCT8, GEMIN5, LARS1, PA2G4, CDK7, NIFK, RSL24D1, EIF3E, THG1L, INTS13, UBE2D2, RPS23, DIMT1, RIOK2, and TTC27 respectively. Previous studies have reported that overexpression of BTF3, CCT8, CDK7, ELF3M, G3BP1, HSPA4, OLA1, and RSL1D1 can contribute to the occurrence and development of CRC ( Goh et al, 2011 ; Zhou et al, 2019 ; Zhou et al, 2021b ; Liao et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022a ; Liu et al, 2022b ; Li et al, 2022 ), overexpression of CCT4 and PA2G4 can contribute to the occurrence and development of LIHC( Li et al, 2021a ; Sun et al, 2022 ), overexpression of DIMT1 and HNRNPA1 can contribute to the occurrence and development of STAD ( Liu et al, 2017 ; Zhu et al, 2022 ), and overexpression of EIF3E and UIMC1 can contribute to the ESCA occurrence and development ( Xu et al, 2018 ; Yang et al, 2018 ). Therefore, we believe that these genes have the potential to be called diagnostic and therapeutic targets of gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%